A multi‐stub loaded compact UWB BPF with a broad notch band and extended stopband characteristics. Issue 4 (6th January 2020) - Kumari, Puja; Sarkar, Pankaj; Ghatak, Rowdra
Abstract: A compact ultrawideband (UWB) bandpass filter (BPF) employing the principle of multiple mode resonance characteristics to create UWB passband with high selectivity and simultaneously having extensive stopband characteristic is presented. Utilizing five stubs attached along with the asymmetric trisection stepped impedance resonator (ATSSIR), the proposed resonator enables seven transmission poles inside the passband. As an additional attributes the projected filter triggers one transmission zero at 5.0 GHz which helps to mitigate WLAN signal interference. No additional circuitry is used to generate a notch band. The proposed prototype of UWB BPF is fabricated and estimated. Simulated and estimated results are in great understanding. The prospective filter displays a deliberate passband from 2.9 to 11.02 GHz. The filter unveils deceptive free wide upper stop band attributes till 25 GHz with least attenuation of 10 dB all through the stop band.